Kuasi Gerakan Sosial: Studi Kasus Aksi 25 Agustus 2025 - Tias, Nadira Cahyaning; Fadhilah, Firyal Nur; Hadinugroho, Dwi Septian; Ummah, Aniqotul; Putra, Teddy Chrisprimanata (Pusat Riset dan Inovasi Nasional, 2026)
This study investigates the phenomenon of quasi-social movements that emerged during the August 25, 2025 protests in Indonesia. Quasi-social movements are defined as forms of public mobilization that appear to arise spontaneously, lack formal organizational structures, and are often leveraged for particular political agendas. Using a qualitative method supported by literature review, this research examines social movement theories, the functions of social media, and the socio-political dynamics that shaped the protests. The findings indicate that the protests were not purely the result of spontaneous civic engagement, but were instead driven by top-down mobilization orchestrated by elite actors through digital narratives, disinformation, and the broader influence of communication technology. This phenomenon signals a shift in the relationship between citizens and the state, including evolving patterns of political participation that do not always follow organized forms. The protests further illustrate how mass mobilization in the digital era can be generated through narrative construction and manipulation of public perception. In conclusion, quasi-social movements represent a new pattern of technology-mediated political expression, highlighting the need for more critical perspectives on modern forms of social mobilization.